Revision of Urubaxia Fennah (Hemiptera: Cercopidae: Ischnorhininae) with description of two new species - Paladini, Andressa; Barão, Kim Ribeiro; Carvalho, Gervásio Silva (Zootaxa, 2016)
We reviewed Urubaxia Fennah, 1968 and described two new species, Urubaxia solo n.sp. and Urubaxia chewie n.sp. from South America. Species of the genus can be easily distinguished by the shape of the paramere, with two divergent processes, and are usually collected in high altitude zones. An identification key and illustrations are provided.